Clinical PET/MRI - Catalano, Onofrio Antonio (Academic Press, 2023)
"Clinical PET/MR presents the state-of-the-art of PET/MR, guiding the reader from how to scan patients, how to read and report the studies, and how keep an eye on what is clinically relevant for a patient's care. Each chapter starts with the clinical scenario and then moves to pertinent imaging, addressing the need of a clinical PET/MR book written by world experts in both clinical and imaging fields. It discusses the clinical application of PET/MR in diverse subspecialties such as head and neck, neurology, cardiovascular, pediatrics, chest, bone, hematology, breast, hepatobiliary pancreatic, genitourinary, gynecology, and gastrointestinal tract. This book is a valuable resource for radiologists, oncologists and members of the biomedical field who need to learn more about clinical applications of PET/MR."--Provided by publisher